The green waves of environmental sustainability in sport - McCullough, Brian P.; Pfahl, Michael E.; Nguyen, Sheila N. (Sport in society, 2016)
The purpose of this paper is to provide a conceptual framework surrounding the typology of environmental sustainability efforts made within the sport industry. We draw from multiple theoretical frameworks (i.e. institutional theory and diffusion of innovation) to understand the increased similarities of environmental sustainability efforts through organizational learning as environmental sustainability efforts become more purposeful and sophisticated across the sport industry. The paper uses examples from various sport organizations and leagues to classify the efforts of sport organizations into waves of sport environmental sustainability efforts and important implications arising from them.